Keunggulan Yesus Kristus Menurut Kolose 1:16-18 - Stepanus Stepanus (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2019)
God’s church as always been facing obstacles and trials throughout history, the church has been challenged in many ways, whether it is from inside or outside, to bring the people’s faith to failure for centuries. Therefore, it cannot be ignored that there have been challenges in a large number. Paul wrote to the church at Colossae to respond to the false teachers that had been slipped into the church. They teach that surrendering to Christ and obedience to the apostles teaching is not sufficient to grant full salvation. These false teachers mixed philosophy and human tradition with the Gospel (Col. 2:8). And asked for the worship of the angels as the mediator between God and men (Col. 2:18). These false teachers demanded certain Jewish practices (Col. 2:16, 21-23) and also justified their fallacies by stating that they had the revelation through visions (2:18). Paul has proven the false teachers’ faults by showing that Christ is not only believers’ savior, but also the head of the church and the Lord, and the Creator. Therefore, it is neither the philosophy nor human wisdom that must be seeded, but Jesus Christ and His Power within a believer’s life that has redeemed and saved believers forever, we need no mediator and we as believers can approach God directly. Believers need only to have faith in Christ, rely on Him, love Him, and live in His presence. We, as believers, may not add rules that are not according to the Gospel.Sejarah kehidupan jemaat Allah selalu mengalami hambatan dan cobaan, gereja ditantang dengan berbagai cara baik dari luar maupun dari dalam untuk menggagalkan iman jemaat. orang percaya dari abad ke abad, maka tidak dapat disangkali telah terjadi banyak tantangan. Paulus menulis kepada jemaat Kolose oleh sebab guru-guru palsu telah menyusup ke dalam gereja. Mereka mengajar bahwa penyerahan kepada Kristus dan ketaatan kepada ajaran para rasul tidak memadai untuk mendapat keselamatan penuh. Para pengajar sesat ini mencampur filsafat dan tradisi manusia dengan Injil (Kol. 2: 8). Dan meminta penyembahan para malaikat sebagai pengantara Allah dan manusia (Kol. 2:18). Para guru palsu ini menuntut pelaksanaan beberapa syarat agama Yahudi (2:16, 21 – 23) serta membenarkan kekeliruan mereka dengan menyatakan bahwa mereka mendapat wahyu melalui penglihatan-penglihatan (2:18). Paulus membuktikan salahnya bidat ini dengan menunjukkan bahwa Kristus bukan saja Juruselamat pribadi orang percaya, tetapi kepala gereja dan Tuhan semesta alam dan pencipta. Karena itu, bukannya filsafat atau hikmat manusia yang diunggulkan, melainkan Yesus Kristus dan Kusa-Nya di dalam kehidupan orang percaya itulah yang menebus dan menyelamatkan orang percaya untuk selama-lamanya, perantara tidak perlu dan kita sebagai orang percaya langsung dapat menghampiri Allah. Orang percaya hanya beriman kepada Kristus saja, bersandar kepada-Nya, mengasihi-Nya dan hidup di hadirat-Nya. Kita sebagai orang percaya tidak boleh menambah aturan-aturan yang bertentangan dengan Injil Kristus.